Syntactic and Semantic Similarities and Discrepancies between Terms of Glossaries for Software Testing - Tebes, Guido; Lew, Philip; Olsina, Luis (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2022)
For software testing, this work performs a comparison and analysis of syntactic and semantic similarities and discrepancies between 3 glossaries. To conduct the study, 8 terminological categories were conceived, which were used to categorize each glossary term, considering the intended semantics. Also, to count the occurrence frequency of a term in the glossaries, a tool was built that also takes into account the matching of synonyms. Then, the analysis of similarities and discrepancies, as well as absent terms for a subset of them, is performed using metrics and expert interpretations. This study identifies several disagreements in standard terminologies that should merit further attention and efforts to promote harmonization amongst the authors/ publishers of these glossaries with the overarching end goal of assisting their readers in learning and understanding the domain of software testing.